(untitled) (Al-Mansour Journal, 2022)
This study presents, efficient FPGA Virtex-5 design flow based QAM modulator using System Generator from Xilinx and MATLAB from mathworks. To allow all digital communication systems for easy adopted with more complicated coding and modulation techniques, the Software Radio (SR) mode has to be used which is extremely in meeting the increasing demands of the wireless communication and mobile industry. However, in this study, the shortest and efficient paths to design an FPGA using MATLAB, Xilinx System Generator, ModelSim, synplify Pro and ISE (Integrated Software Environments ) software tools is introduced. The floating point design in MATLAB has been moved to fixed point values using the most attractive and friendly Xilinx DSP system generator software a model based approach associated with assistance software from Mathworks and Synplicity. Result obtained shows an important utilization in Look Up Table (LUT) and Slices in FPGA Virtex-5 design. This demonstrates the ability of less power consumption